Analisis Speaking Siswa Kampung Bahasa Bloom Bank Melalui Treatment Permainan 2 Dimensi - Iwan Budiarso (Universitas Indraprasta PGRI Jakarta, 2017)
This research is an analysis of students’ speaking skill by using a 2D game treatment technique. The object of this research is 30 students from an educational institution Kampung Bahasa Bloom Bank Indonesia located in Ciracas, East Jakarta. This educational institution is a non-profit organization conducting English teaching for students from poor families. The purpose of this research is to introduce a teaching technique in the form of treatment of 2D game to instructors, tutors and teachers during English learning and teaching process in Kampung Bahasa Bloom Bank. The method employed in this research is a descriptive method with qualitative approach by drawing a conclusion from the analysis of the English speaking skill scores of students having received the treatment of 2D game. From the analysis result, it can be concluded that the students’ speaking skill scores are good. It means that this treatment has been successfully applied in Kampung Bahasa Bloom Bank environment to improve the speaking skill of the students.